Hepatitis B Testing and Vaccination in Immigrants Attending English as a Second Language Classes in British Columbia, Canada - Hislop, T Gregory (2009)
BACKGROUND: Hepatitis B virus (HBV) is a growing health issue in Canada, especially given that population growth is now largely the result of immigration. Immigrants from countries with high HBV prevalence and low levels of HBV vaccination have an excess risk of liver disease and there is a need for increased diligence in HBV blood testing and possibly vaccination among these populations. OBJECTIVE: This study describes the sociodemographic characteristics associated with a history of HBV testing and HBV vaccination in immigrants from several countries with high HBV prevalence who are attending English classes. METHODS: 759 adult immigrants attending English as a Second Language classes completed a self-administered questionnaire asking about sociodemographic characteristics and history of HBV testing and HBV vaccination. Descriptive statistics and adjusted ORs were calculated to explore these associations. RESULTS: 71% reported prior HBV testing, 8% reported vaccination without testing, and 21% reported neither testing nor vaccination. Age, education and country of birth all showed significant effects for both testing and vaccination. CONCLUSIONS: Health care practitioners need to be cognizant of HBV testing, and possibly vaccination, in some of their patients, including immigrants from countries with endemic HBV infection. Infected persons need to be identified by blood testing in order receive necessary care to prevent or delay the onset of liver disease as well as to adopt appropriate behaviours to reduce the risk of transmission to others. Close contacts of infected persons also require HBV testing and subsequent vaccination (if not infected) or medical management (if infected).